Peran Musyrif Tahfizh dalam Penguatan Hafalan Mahasiswa di Sekolah Tinggi Ilmu Al-Qur’an (STIQ) Isy Karima Karanganyar - Putra, Rizky Pratama; Fatimah, Meti; Rumaf, Arafiq Fathul Haq (Asatiza: Jurnal Pendidikan, 2023)
Memorizing the Qur'an is not just adding to memorization, but how to maintain memorization that has been memorized. Isy Karima Karanganyar High School of Al-Qur'an Science (STIQ) is one of the Islamic tertiary institutions that organizes tahfihz Al-Qur'an as the content contained in the curriculum and all students are required to memorize the Al-Qur'an as their trademark. The research objective was to determine the role of Musyrif Tahfiz in Strengthening Student Memorization. The method used in this research is descriptive qualitative research in which data collection uses observation, interviews and documentation. The results of the study showed that first, Strengthening Al-Qur'an memorization with the halaqoh system, second, Reinforcement of Al-Qur'an memorization with the takrir method is quite effective through four techniques namely, the takrir technique together, takrir individually, takrir in prayer and takrir in the presence of musyrif.